Conditions for the Formation of an Educational Hub for the Implementation of International Educational Programs in Uzbekistan - N. M. Ibragimova; Kh. V. Dilfuza (Высшее образование в России)
In response to the demands of globalization, many countries have focused their efforts on pursuing a policy to create international and regional educational centers, transform their higher education systems, enhance their international activities, and expand joint programs of universities as tools to increase their competitiveness. The purpose of this article is to study the factors affecting competitiveness in the formation of an educational hub, basing on the world experience in educational hubs creation in the context of of higher education institutions globalization and to identify the priority measures to stimulate the integration of international educational programs and expand the universities’ international activities in Uzbekistan. As an empirical base, we used the results of the studies of foreign countries that successfully achieved their goals of forming regional educational hubs, as well as open data on the leading universities in the Central Asia and Uzbekistan’s positions in international rankings on the attractiveness for foreign students. The methodological basis of the research is comparative and systematic analysis, case method, content analysis of websites of leading universities in Central Asia, expert assessment. The theoretical and methodological foundations and factors affecting the competitiveness of the educational activities of the university in the context of globalization and modernization of higher education are considered. Based on the comparative analysis of a significant array of academic and analytical materials to determine the factors of supply and demand (push-pull factors), implemented strategies for the transformation of universities in a group of dynamically developing countries, the authors provide an assessment factors affecting the competitiveness while creating international and regional educational centers of higher education in Uzbekistan, as well as give recommendations on organizational, economic, institutional mechanisms for transforming the higher education system of the republic into a hub for the implementation of international educational programs in the Central Asia.